Carbon-coated MoS2 nanosheets as highly efficient electrocatalysts for the hydrogen evolution reaction. (11th December 2015) - Dou, Shuo; Wu, Jianghong; Tao, Li; Shen, Anli; Huo, Jia; Wang, Shuangyin
Abstract: As a green and highly efficient energy resource, hydrogen (H2 ) has attracted much attention in recent years. Electrochemical water splitting is an economic process to generate H2 . MoS2 is a promising candidate to replace traditional Pt-based electrocatalysts for the hydrogen evolution reaction (HER) under acidic conditions. But low electrical conductivity is one of bottlenecks for the large-scale application of MoS2 . In this work, a carbon-coated MoS2 hybrid electrocatalyst was prepared with a chemical vapour deposition (CVD) approach to improve the electrical conductivity of MoS2 . In addition to the surface-coating carbon, a small graphene-like layer could also be inserted into the interlayers of MoS2 during the CVD process which resulted in more active sites being exposed in MoS2 . Enhanced electrical conductivity and more exposed active sites lead to excellent HER activity.